1983
DOI: 10.1515/cclm.1983.21.12.835
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Serum Guanosine Deaminase Activity in Liver Disease

Abstract: Summary: An assay for the estimation of guanosine deaminase is described. The method employs guanosine äs Substrate and after incubation of serum and Substrate at 22 °C for 18 h the ammonia Hberated is estimated using the Berthelot reaction. Absorbance is measured at 625 nm and the catalytic activity read from a Standard curve obtained using ammonia Standards. The method provides reproducible measurement of serum guanosine deaminase. The results obtained using 'normal' sera have been used to calculate the 'nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Preliminary results of Jones et al (1983) suggested that GDA increased in hepatitis and in patients with liver metastases, but normalized in all other liver diseases including cirrhosis and obstructive jaundice. However, we could not observe any statistical difference between acute and chronic hepatitis B cases.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results of Jones et al (1983) suggested that GDA increased in hepatitis and in patients with liver metastases, but normalized in all other liver diseases including cirrhosis and obstructive jaundice. However, we could not observe any statistical difference between acute and chronic hepatitis B cases.…”
Section: Discussionmentioning
confidence: 99%